Targeted therapy for the post-operative conjunctiva : SPARC silencing reduces collagen deposition - Seet, Li Fong (2020)
Background: To develop targeted antifibrotic therapy for glaucoma filtration surgery; this study determines the effectiveness of small interfering RNA (siRNA) to reduce in vivo secreted protein acidic and rich in cysteine (SPARC) expression using the mouse model of conjunctival scarring. Methods: Experimental surgery was performed as described for the mouse model of conjunctival scarring. Scrambled (siScram) or Sparc (siSparc) siRNAs, loaded on layer-by-layer (LbL) nanoparticles, were injected into the conjunctiva immediately after surgery. Expression of Sparc, Col1a1, Fn1 and Mmp14 was measured by real-time PCR and immunoblotting on days 7 and 14 postsurgery. Live imaging of the operated eyes was performed using slit lamp, anterior segment-optical coherence tomography and confocal microscopy. Tissue pathology was evaluated by histochemical and immunofluorescent analyses of operated conjunctival cryosections. Tissue apoptosis was quantitated by annexin V assay. Results: siSparc, delivered via expanded LbL nanoparticles, significantly inhibited Sparc transcription in both day 7 (2.04-fold) and day 14 (1.39-fold) treated tissues. Sparc suppression on day 7 was associated with a significant reduction of Col1a1 (2.52-fold), Fn1 (2.89-fold) and Mmp14 (2.23-fold) mRNAs. At the protein level, both SPARC and collagen 1A1 (COL1A1) were significantly reduced at both time points with siSparc treatment. Nanoparticles were visualised within cell-like structures by confocal microscopy, while overt tissue response or apoptosis was not observed. Conclusions: SPARC targeted therapy effectively reduced both SPARC and collagen production in the operated mouse conjunctiva. This proof-of-concept study suggests that targeted treatment of fibrosis in glaucoma surgery is safe and feasible, with the potential to extend to a range of potential genes associated with fibrosis.